Publisher Correction: Diverse populations of local interneurons integrate into the Drosophila adult olfactory circuit. Issue 1 (December 2018) - Liou, Nan-Fu; Lin, Shih-Han; Chen, Ying-Jun; Tsai, Kuo-Ting; Yang, Chi-Jen; Lin, Tzi-Yang; Wu, Ting-Han; Lin, Hsin-Ju; Chen, Yuh-Tarng; Gohl, Daryl; Silies, Marion; Chou, Ya-Hui
The original version of this Article contained errors in Figs. 4 and 6. In Fig. 4, panel a, text labels UAS-FLP and LexAop2>stop>myr::smGdP-HA were shifted upwards during typesetting of the figure, and in Fig. 6, panel h, the number 15 was incorrectly placed on the heat map scale. These have now been corrected in both the PDF and HTML versions of the Article.